2013
DOI: 10.1002/jmri.23994
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial flow velocity distribution and flow coherence using four‐dimensional FLOW MRI: A pilot study investigating the impact of age and Pre‐ and Postintervention atrial fibrillation on atrial hemodynamics

Abstract: Flow-sensitive MRI shows that patients with a history of AF had global hemodynamics in the LA similar to those of age-matched volunteers. Additional studies with larger cohorts of AF patients and correlation with outcome are needed to further investigate the potential of atrial 4D flow MRI to flow patterns indicative of stroke risk in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 22 publications
5
73
0
Order By: Relevance
“…9397 4D flow MRI is uniquely suited for evaluation of LA flow velocities (an index of atrial function) as it can provide blood velocity in 3 orthogonal directions with full volumetric coverage of the LA throughout the cardiac cycle with a single, free-breathing 10–15 minute acquisition. 94, 9799 The 3D segmentation of LA volume enables quantitative analysis of 3-directional velocities inside the entire LA over all time frames of the cardiac cycle. 99 Recent studies demonstrated low inter-observer variability and good test-retest reliability for the quantification of blood flow velocities and other hemodynamic parameters.…”
Section: Techniques For Evaluating Atrial Myopathy - Substrate For Afmentioning
confidence: 99%
See 2 more Smart Citations
“…9397 4D flow MRI is uniquely suited for evaluation of LA flow velocities (an index of atrial function) as it can provide blood velocity in 3 orthogonal directions with full volumetric coverage of the LA throughout the cardiac cycle with a single, free-breathing 10–15 minute acquisition. 94, 9799 The 3D segmentation of LA volume enables quantitative analysis of 3-directional velocities inside the entire LA over all time frames of the cardiac cycle. 99 Recent studies demonstrated low inter-observer variability and good test-retest reliability for the quantification of blood flow velocities and other hemodynamic parameters.…”
Section: Techniques For Evaluating Atrial Myopathy - Substrate For Afmentioning
confidence: 99%
“…94, 9799 The 3D segmentation of LA volume enables quantitative analysis of 3-directional velocities inside the entire LA over all time frames of the cardiac cycle. 99 Recent studies demonstrated low inter-observer variability and good test-retest reliability for the quantification of blood flow velocities and other hemodynamic parameters. 100102 We have demonstrated the potential for this technique to identify different flow patterns in patients with AF, even for those not in sinus rhythm during imaging.…”
Section: Techniques For Evaluating Atrial Myopathy - Substrate For Afmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy young subjects with normal rhythm, blood pressure, and flow, the LA appears to avoid any sustained stasis of blood. 36 Atrial thrombosis was related with some factors such as stasis of blood flow and hypercoagulable status. 8 AF is closely associated with these factors and an increased risk of both LA and RA thrombosis, 5,37 but the number…”
Section: L-arginine Treatment Increased No Production and Decreased Tmentioning
confidence: 99%
“…4D Flow CMR has previously been applied for analysis of blood flow in both healthy subjects and patients regarding the ventricles (47,60,61,63,66,67) and the atria (68,69) of the heart, heart valves and valve prostheses (70)(71)(72), aorta (73)(74)(75)(76)(77), pulmonary vessels (78), and other arteries and veins in the body (79,80). Quantification of flow can be performed from measurements of basic blood flow volumes and velocities to advanced estimations of derived hemodynamic markers such as turbulent kinetic energy (TKE) (81)(82)(83), pressure gradients (84)(85)(86), wall shear stress (87,88) and hemodynamic force (89).…”
Section: Artifactsmentioning
confidence: 99%